THE EFFECT OF PERIOPERATIVE AND PROPHYLACTIC ANTIBIOTICS AGAINST THE INCIDENCE OF UTI AND SURGICAL SITE INFECTIONS AFTER HYPOSPADIAS SURGERY - Kusuma, Raditya; Renaldo, Johan; Djojodimedjo, Tarmono; Hardjowijoto, Sunaryo (Indonesian Urological Association, 2017)
Objective: The aim of this study is to analyze the effect of perioperative and prophylactic antibiotics against the incidence of urinary tract infections (UTI) and surgical site infections (SSI) after hypospadias surgery (hypospadias repair operation). Materials & Methods: This study is an observational study of explanation with 24 hypospadias patients (2 groups) during the period of October 2015 to February 2016. Samples were divided into two groups, 12 patients received prophylactic antibiotics and 12 patients received perioperative antibiotics (random sampling). Inclusion criteria included patients with glandular hypospadias to proximal penile hypospadias, aged 6 months until 15 years and underwent hypospadias surgery with one surgical technique namely Tubularized Incised Plate (TIP). The examination of urine culture and evaluation of the wounds were performed on day 4, 10, and 20 day after surgery to determine the incidence of urinary tract infections and surgical site infections. Results: There is no significant difference in the incidence of UTI on on day 4, 10 and 20 in perioperative group and prophylaxis group with p=0.282 and p=0.500 at day 4 and 10 (p>0.05). There is no significant difference in the incidence of SSI on day 4, 10 and 20 in the group of perioperative antibiotic and prophylactic antibiotic with p=0.680 and p=0.217 at day 4 and 10 (p>0.05). Conclusion: There is no effect of the prophylactic antibiotic as well as perioperative antibiotic treatment on the incidence of UTI and SSI